A stirring parade of political villains - Wayne Hope (Asia Pacific Network, 2007)
"Over subsesquent chapters, Trotter explains how key phases of New Zealand hisotry were shaped by institutionalised power and political struggle. Along the way major villains are identified, paraded and held to account. During the colonisation phase we observe how Edward Wakefield's land speculation schemes overruled the customary rights of Maori and exploited the aspirations of lowly settlers..."